Become a Wise Millennial in Respect of Technological Development in an Islamic Perspective - Indriani, Risa Nur; Nurhafizha, Aliya; Erliani, Erlin; Nursyahla, Natasya Putri Sabrina; Aeini, Ani Nur (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The development of increasingly advanced technology is regretted because it has positive and negative impacts. However, the progress and development of technology does not always have a positive impact, there are some irresponsible individuals who use technology as material to carry out their bad actions. Millennials or young people who live in the era of digitalization and globalization do have big responsibilities and must also have principles in living life in the digitalization era that needs to choose a wise attitude in responding to this technological advancement. Counseling which was held on Tuesday 02 November 2021, took place using via zoom with the theme of counseling "Becoming Millennials who are Wise in Responding to Technological Developments in an Islamic Perspective" in the material explaining how to be wise millennials in responding to technological developments in an Islamic perspective in the results of the questionnaire stated that the average use of technology. The rapid development of technology is not accompanied by a critical culture of looking at problems, feeling great to be the first to disseminate information without seeing the truth of the information. This counseling activity was attended by 45 general students from several universities in the West Java area, regarding the steps to identify hoaxes, the pretest results showed 22.7% knew the steps to identify hoaxes, 40.9% knew enough, 27.3% did not know, 9.1% did not know. After counseling the posttest data showed: 76.9% understood, 23.1% quite understood. Hopefully, people can use the mass media still in an Islamic perspective such as being tabayyun, being free but responsible, upholding objectivity and honesty, as well as presentation that is correct and does not cause misinterpretation.